2009
DOI: 10.2214/ajr.08.2285
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Thickening Along the Articular Surface of the Rotator Cuff Consistent With the Rotator Cable: Identification With MR Arthrography and Relevance in Rotator Cuff Evaluation

Abstract: On non-ABER MR arthrographic images, thickening along the articular side of the supraspinatus and infraspinatus tendons presumed to represent the rotator cable suggests the presence of a partial-thickness rotator cuff tear. On ABER images, the cable is well defined in intact and torn rotator cuffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 13 publications
0
19
0
6
Order By: Relevance
“…Compared to previous papers that used magnetic resonance arthrography to evaluate rotator cable consistency [8e10], US demonstrated an increased capability of demonstrating rotator cable analysis in living subjects [9]. Conversely, Kask et al [10] successfully detected rotator cable in 6/7 magnetic arthrographies (85.7%) performed on cadaveric shoulders.…”
Section: Discussionmentioning
confidence: 91%
“…Compared to previous papers that used magnetic resonance arthrography to evaluate rotator cable consistency [8e10], US demonstrated an increased capability of demonstrating rotator cable analysis in living subjects [9]. Conversely, Kask et al [10] successfully detected rotator cable in 6/7 magnetic arthrographies (85.7%) performed on cadaveric shoulders.…”
Section: Discussionmentioning
confidence: 91%
“…The rotator cable has been described in most shoulders with an intact rotator cuff predominantly on MRI. 10,11 In a recent study of 108 asymptomatic patients, the rotator cable was identified on US in 99% of shoulders. Most of the rotator cables (95%) were located within 13.4 mm from the greater tuberosity (►Figs.…”
Section: Rotator Cuff Rotator Interval and Coracohumeral Ligamentmentioning
confidence: 99%
“…If tolerated by the patient, ABER positioning can add diagnostic confidence. 10,[89][90][91][92][93][94] In the ABER position, the anterior band of the inferior glenohumeral ligament is stretched, allowing better evaluation of the anterior inferior labroligamentous complex. 91,93,94 Tendon delamination and undersurface partial-thickness cuff tears are easier to detect in the ABER position because the supraspinatus tendon is relaxed 89,94 (►Fig.…”
Section: Imaging Protocols (Mri Imaging Parameters and Sequences)mentioning
confidence: 99%